Content consumption patterns new media by the population of Belarus: theoretical and methodological aspect of the construction - Бельский, Александр Михайлович (Journal of the Belarusian State University. Sociology, 2021)
The article indicates the relevance of the study of media practices of the population with the exit to the formation of relatively stable models of media consumption in the conditions of the reflexive growth of the impact of such a player in the information field as new media. The characteristics of the features of the typologisation and classification of social subjects are given, possible approaches to typologisation and classification are reflected, as well as those contradictions that may arise during the implementation of the designated research procedures. A two-stage scenario for the implementation of the study of media consumption of the population of Belarus with the derivation of social portraits of consumers of traditional and new media finds its justification, the content of these constructs is reviewed. Using a practical example of an independent representative sociological research, the possibilities of factor and cluster analysis in empirical typology using software are demonstrated with a detailed description of the implementation of procedures and proposals for ways to resolve possible difficulties in the course of their application. The author presents and interprets the author’s five-component typology of media consumption models with an exit to the possibility of its application in wide practice with the available array of primary sociological information on the basis of calculating a number of additional indicators. The results obtained can find their application in the sociology of mass communication and the media and are addressed to specialists in the field of sociology of public opinion, theories of the information society, as well as the theory and methodology of sociology.